Optimalisasi Pengenalan Dan Partisipasi Siswa Dalam Olahraga Tradisional Di SMA Negeri 1 Bergas - Muhamad Nur Syafi’i (Hikamatzu | Journal of Multidisciplinary, 2024)
This research aims to analyze Optimizing the Introduction and Participation of Students in Traditional Sports at SMA Negeri 1 Bergas. This type of research is qualitative with a case study approach. This approach involves an in-depth analysis of one or several cases that represent concrete examples of the phenomenon being studied. Data were collected using observation, interviews. Data analysis using mile Huberman analysis with data reduction, data display and conclusion. In general, researchers can say that the implementation of community service at SMA Negeri 1 Bergas with the theme Socialization of Sreng Traditional Sports as a Regional Asset has been quite effective from the preparation stage to implementation. The enthusiasm, response and support from the school for this activity was enormous, starting from the Principal as leader, the teacher council involved to the students at SMA Negeri 1 Bergas. The re-introduction of the traditional game Sreng presented by the researcher was accepted by the participants as a very enjoyable activity, so that during the implementation, both the material delivery session and the practice of the traditional game ran smoothly. The results that researchers were able to convey regarding this activity were very effective and had an impact, especially on students in the SMA Negeri 1 Bergas environment. Previously it was rare to see students playing traditional games during recess or when there were no lessons, but now you can find some students starting to preserve it by playing traditional games in the school environment without feeling awkward